(untitled) (PerCursos, 2023)
This article aims to analyze the mobility issue of residents in peripheral areas, focusing on the Baixada Fluminense region through a case study of the Belford Roxo rail line. The poor quality of life experienced by these residents is directly linked to the railway transportation, which fails to meet the population’s demand to fully exercise their right to mobility within the urban context. The research is grounded in a comprehensive review of specialized literature, supported by official data and relevant studies concerning the mobility challenges in the area under analysis. At the end of the study, deficiencies and vulnerabilities inherent to the transportation system provided by Supervia are identified. These issues are exacerbated by the daily adversities faced by citizens in the periphery of Fluminense: the constant delays and overcrowding of train schedules, significantly limiting the opportunities for residents to fully experience urban life.